AN ANALYSIS OF SLANG LANGUAGE TYPES IN "THE DUFF" MOVIE" - Herman (Wiralodra English Journal, 2020)
The purpose of this study was to determine the type of use of slang language. The types of slangs were analyzed from â€œThe Duffâ€ movie. Theories used in this research were Paltridge (2004) about the types of slang language and Yanhong (2013) about the functions of slang. This study was conducted by using a descriptive qualitative method. The data was from a movie entitled â€œThe Duffâ€ in the year of 2015 with genre of teen or comedy. After conducting the analysis, this study showed that there were six slang languages from eleven type of slang language. They were society, cockney, workmenâ€™s, public school and university, public house, and theater. Society was found as the most dominant slang language with society with 41 data (54,6%), public house with 20 data (26,6%), workmenâ€™s with 6 data (8 %), cockney with 5 data (6,6%), theater with 2 data(2,6%), and public school and university with 1 data (1,3%). Finally, the researcher hopes that this study will be useful for the future improvement of studying literature, especially about slang language